2021
DOI: 10.1016/j.compag.2020.105902
|View full text |Cite
|
Sign up to set email alerts
|

Short term soil moisture forecasts for potato crop farming: A machine learning approach

Abstract: Agricultural decision-making is crucial for future yields. In the context of smart farming, grower combine information from sensors located close to their crops with agronomic models to help them to better understand their crops. Irrigation management is therefore based on extrapolation of data and/or agronomic model responses. This problem can be seen as a learning task for which machine learning techniques have proven their relevance in many and diverse applications. In this paper we place ourselves in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…The models’ output was the estimated soil matric potential at 0.20 m depth, where thresholds can be used in practice to trigger irrigation events. Gumiere et al (2020) and Dubois et al (2021) also explored machine learning models for predicting soil matric potential in cranberry and potato crops, respectively, for irrigation management. In Gumiere et al (2020) , a Random Forest (RF) model with rainfall, reference evapotranspiration and soil matric potential measurements at 0.10 m as input data predicted hourly soil matric potential with an R 2 of 0.58.…”
Section: Discussionmentioning
confidence: 99%
“…The models’ output was the estimated soil matric potential at 0.20 m depth, where thresholds can be used in practice to trigger irrigation events. Gumiere et al (2020) and Dubois et al (2021) also explored machine learning models for predicting soil matric potential in cranberry and potato crops, respectively, for irrigation management. In Gumiere et al (2020) , a Random Forest (RF) model with rainfall, reference evapotranspiration and soil matric potential measurements at 0.10 m as input data predicted hourly soil matric potential with an R 2 of 0.58.…”
Section: Discussionmentioning
confidence: 99%
“…Rahmati et al (2020) revealed that RF had better classification ability than SVM when predicting agricultural droughts in Australia. Dubois et al (2021) reported that RF and SVM had better quantitative prediction ability than ANNs for forecasting soil moisture in the short-term. In other fields, Uddin et al (2019) unveiled that in disease detection, RF had the highest chance to show excellent classification capability (with an AUC over 0.8), followed by SVM, NB, ANNs, KNN.…”
Section: Discussionmentioning
confidence: 99%
“…Topic Solution [47] Soil Nutrition [51] Soil Classification [48] Soil Detection System [49] Soil Humidity Sensing [52], [53] Soil Moisture Prediction and Forecast [54] Soil Moisture Evaluation [55], [56] Soil Prediction [57] Soil Estimate Soil Moisture [50] Soil Analysis Kwok and Sun [59], On technology in ML can be used for learning and is very important in agriculture. In recent years, many studies have taken advantage of machine learning as part of AI.…”
Section: Referencesmentioning
confidence: 99%